Effect of magnetic field on double layer in argon helicon plasma. Issue 2 (5th November 2020) - Yang, Kaiyi; Cui, Ruilin; Zhu, Wanying; Wu, Zhiwen; Ouyang, Jiting
Abstract: The electric double layer in argon helicon plasma by using floating electrostatic probe and local optical emission spectroscopy under different external magnetic field was investigated. Results show that electrons generated in the plasma source can be magnetized by the magnetic field and transported by the gradient of diverging magnetic field in the diffusion chamber, giving rise to the hollowed distribution of electron temperature. The electron temperature on axis has a sudden decrease, leading to the sudden decrease of plasma density as well as the plasma potential, forming a double layer structure. The position of double layer moves along with the position of diverging magnetic field, and the potential drop increases along with the strength of magnetic field. The structure of the external magnetic field plays the decisive factor for the double layer in helicon plasma.